The Theoretical Nature of Systems Thinking. Perspectives on Systems Thinking in Biology Education - Verhoeff, Roald P.; Knippels, Marie-Christine P. J.; Gilissen, Melde G. R.; Boersma, Kerst T. (Frontiers in Education, 2018)
Systems thinking has become synonymous to developing coherent understanding of complex biological processes and phenomena from the molecular level to the level of ecosystems. The importance of systems and systems models in science education has been widely recognized, as illustrated by its definition as crosscutting concept by the Next Generation Science Standards (NGSS, 2013). However, there still seems no consensus on what systems thinking exactly implies or how it can be fostered by adequate learning and teaching strategies. This paper stresses the theoretical or abstract nature of systems thinking. Systems thinking is not just perceived here as ‘coherent understanding’, but as a learning strategy in which systems theoretical concepts are deliberately used to explain and predict natural phenomena. As such, we argue that systems thinking is not to be defined as a set of skills, that can be learned ‘one by one’, but instead asks for consideration of systems characteristics and the systems theories they are derived from. After a short elaboration of the conceptual nature of systems thinking, we portray the diversity of educational approaches to foster systems thinking that have been reported in the empirical literature. Our frame of analysis focuses on the extent to which attention has been given to the matching of natural phenomena to one of three systems theories, the integration of different systems thinking skills and the role of modelling. Subsequently, we discuss the epistemological nature of the systems concept and we present some conclusions on embedding systems thinking in the secondary biology curriculum.